ASSESSING POSYANDU CADRES’ READINESS IN IMPLEMENTING INTEGRATED PRIMARY HEALTH SERVICES IN YOGYAKARTA, INDONESIA - Tri Siswati; Yustiana Olfah; Jutharat Attawet; Nurhidayat Nurhidayat; Lukman Waris (Jurnal Administrasi Kesehatan Indonesia)
Background: The readiness of Posyandu (a community-based health service) cadres’ to implement the Integrated Primary Health Services (Integrasi Layanan Primer/ILP) is vital to advancing preventive and promotive care.